APPLICATION OF STEREOLOGICAL METHODS TO STUDY THE WHITE MATTER AND MYELINATED FIBERS THEREIN OF RAT BRAIN - Yang, Shu; Li, Chen; Zhang, Wei; Wang, Weiwei; Nyengaard, Jens R; Tang, Yong (Image Analysis and Stereology, 2011)
An efficient and unbiased stereological method was applied to estimate the white matter volume, the total volume, total length and mean diameter of the myelinated fibers in the white matter and the total volume of the myelin sheaths in the white matter of rat brain. The white matter volume was obtained with the Cavalieri principle. Four tissue blocks were sampled from the entire white matter in a uniform random fashion. The length density of the myelinated fibers in the white matter was obtained from the isotropic, uniform, random sections ensured by the isector. The volume density of the myelinated fibers in the white matter was estimated by point counting. The total length and the total volume of the myelinated fibers in the white matter were estimated by multiplying the white matter volume and the length density and the volume density of the myelinated fibers in the white matter, respectively. The size of nerve fibers was derived by measuring the profile diameter perpendicular to its longest axis. The results were satisfactory in the sense that the sampling variance introduced by the stereological estimation procedure was a minor fraction of the observed variance. The comparison of the white matter and the myelinated fibers in the white matter between rat brain and human brain was also made in the present study.